Comparison of the effects of abdominal massage and osteopathic manipulative treatment home program on constipation in children with cerebral palsy - ACAR, GÖNÜL (My University, 2024)
Background and Aim: The aim of this study is to compare the effects of osteopathic manipulative therapy home program (OMT-H) versus abdominal massage home program (AMHP) in treating constipation in children with cerebral palsy (CP). Methods: Twenty-nine children with CP with a mean age of 12.2 ± 3.76 years, who were constipated and were not on medication, were divided into three randomized groups: (i) control group (n = 10), (ii) AMHP (n = 10), and (iii) OMT-H (n = 9). In AMHP and OMT-H groups, treatment was applied as 20-min sessions every other day for 10 sessions for 3 weeks. Modified Constipation Assessment Scale (MCAS), Rome III criteria, and the Bristol Stool Form Scale (BSFS) were used for evaluation before treatment and once a week during treatment. Results: While there was no change in constipation symptoms in the control group, there was an improvement in constipation symptoms after treatment in the AMHP and OMT-H groups (AMHP, P = 0.003; OMT-H, P = 0.000014). While the treatment showed to be effective from the first week in the OMT-H group, the change in BSFS (P = 0.026) and MCAS sub-parameters was found to be superior. Conclusion: AMHP and OMT-H are effective and beneficial in treating constipation. In children with CP, OMT-H was found to be quicker and more successful compared with AMHP. The OMT-H can be effectively used in clinical practice in relieving constipation in CP.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; GASTROENTEROLOJİ VE HEPATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; GASTROENTEROLOGY & HEPATOLOGY; Hepatoloji; Gastroenteroloji; Hepatology; Gastroenterology; abdominal massage; cerebral palsy; constipation; osteopathic manipulative treatment; physiotherapy